Peran Guru Pendidikan Agama Kristen dalam Mencegah Kecanduan Gadget pada Remaja - Andrika Telaumbanua; Afriani Damaris Purba; Piter Imanson Damanik; Elieser Marampa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The role of Christian religious education teachers is crucial in guiding teenagers to use gadgets wisely and in line with Christian teachings. Uncontrollable use of gadgets can lead to addiction, which in turn can damage the understanding of Christian values and moral behavior of adolescents. The purpose of this study is to determine the role of Christian Religious Education Teachers in Preventing Gadget Addiction in Teenagers. The results of this study show that (1) Christian Religious Education teachers have a very important role in helping adolescents understand and overcome the problem of gadget addiction through moral and spiritual education based on biblical values. (2) Christian Religious Education teachers need to collaborate with parents in preventing and overcoming gadget addiction in adolescents (3) Christian Religious Education teachers, play a role in guiding adolescents in dealing with the use of gadgets wisely, as well as highlighting strategies that can be used to achieve this goal including effective communication. Thus, Christian Religious Education Teachers as a foundation in overcoming and building awareness of adolescents so that adolescents are not affected in the excessive use of gadgets.